Correlaciones del orden de palabras en las lenguas amerindias - Quesada Castillo, Félix (2003)
This article reports on the results of preliminary empirical research of word order correlations. Based on a small sample, the results support the Branching Direction Theory which was developed by Dryer 1992. In this work, Dryer argues against the Head-Dependent Theory. According to· this, the word order correlations reflect a tendency for dependénts to precede heads in OV languages and follow heads in VO languages. Even though the sample contains ·VO languages (Mochica and Ashaninka), the examination of the data shows a tendency to words the OV order of languages, that is, they tend to consistent direction of left·branching.